RELATION OF THE FARMERS INOVATIVENESS LEVEL TO THE LEVEL OF ORGANIC PRACTICE SUSTAINABILITY IN SUNGAI RENGAS VILLAGE, SUNGAI KAKAP, KUBU RAYA, WEST KALIMANTAN (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
The success of agricultural development is strongly related to how far information of innovation reached the farmers. Here lies the importance of agricultural outreach communication by observing the level of farmers innovativeness in practicing organic cropping pattern. This research observes the relation between farmers innovativeness with the organic farming practice level of sustainability. The innovativeness variables being observed are the social-economy, individual and communication activities. Variables being observed in the organic farming practice is the implementation of organic farming principles such as over three years land conversion, usage of local seeds, the use of organic fertilizer, the use of non chemical pesticides and division of land and irrigation from the non-organic farming. This research was carried in the Sungai Rengas Villa, Sungai Kakap Sub-district, Kubu Raya District, West Kalimantan. The research employs explanatory research method, with data collection by survey. This research took samples of 36 respondents. Primary data in the research was collected through questionnaires accompanied by interviews to a number of organic farmer in Sungai Rengas Village, Sungai Kakap Sub-district, Kubu Raya District. Secondary data was taken from the local government institution (village/sub-district), Department of Lands, Agricultural and Plantation Office, or related statistical data accessible in the internet. After the data was collected, it was coded and input into SPSS.